OPTIMIZING FORMULA OF FAST DISINTEGRATING TABLET NATRIUM DICLOFENAC β-CYCLODEXTRIN INCLUSION COMPLEX WITH CROSPOVIDONE AS THE SUPERDISINTEGRANT AND MICROCRYSTALLINE CELLULOSE PH 102 AS THE FILLER BINDER - Wahyu Irawan; T.N. Saifullah Sulaiman (Majalah Farmaseutik, 2016)
Natrium diclofenac (Na-DCF) is one of non-steroidal anti-inflammatory drug (NSAID) that have a bitter taste. The inclusion complex of NaDCF with β-cyclodextrin (BSD) can be made to mask the unpleasant taste. The inclusion complex of natrium diclofenac-β-cyclodextrin (NaDCFBSD) was prepared by spray drying method in 1:1 molar ratio. NaDCF, BSD, and NaDCF-BSD inclution complex was characterized by Fourier Transform Infrared Spectroscopy (FTIR). NaDCF-BSD complex was formulated into Fast Disintegrating Tablet (FDT) by optimizing crospovidone as superdisintegrant and microcrystalline cellulose (MCC) PH 102 as filler binder. FDTs were made by direct compression method. A respond test of taste was conducted on the FDT of optimum formula. The optimum physical properties of FDTs were produced by formulating 5,79% crospovidone and 39,21% MCC PH 102. The respond test of taste results showed that FDT with NaDCF in inclution complex have a better taste than FDT with NaDCF without inclusion complex.